A Visual Representation to Quantitate, Diagnose, and Improve Creativity in Insight Problem Solving. (25th January 2016) - McCaffrey, Tony
Abstract: A new visual representation for insight problems permits 22 new quantitative measures; which leads to a detailed diagnosis of a person's (or team's) creative weaknesses; which then leads to prescribing targeted, effective counter‐techniques for each weakness. Currently, only two measures are consistently used for insight problem solving: the number of problems solved and the time to solve the problems. These coarse measurements do not reveal the intricate dynamics of solving insight problems. Furthermore, four commonly used creativity measures (i.e., fluency, originality, flexibility, and elaboration ) are often not applied to insight problems. This new visualization permits the easy application of all four creativity measures. I challenge creativity researchers to help determine which of the 22 proposed quantitative measures are the most diagnostic for insight problem solving in isolation and, in a weighted linear combination, which might yield an effective quotient (i.e., overall measure) of insight problem solving ability.